IMPLIKASI SUPERVISI PENGAWAS SEKOLAH MELALUI DARING DI SEKOLAH DASAR KABUPATEN ROKAN HILIR - Srimulyati; Zulfan Saam; Sri Kartikowati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aimed to describe: 1) the school supervisors' plan for the online supervision at Elementary Schools in Kabupaten Rokan Hilir, 2) the implementation of online supervision conducted by the school supervisors at Elementary Schools in Kabupaten Rokan Hilir, 3) the evaluation of the result of online supervision at Elementary Schools in Kabupaten Rokan Hilir. This study was descriptive qualitative research with descriptive qualitative data. Data were collected through observation, interviews, and online documents. Informants/subjects in the study were the principals and teachers. This study was carried out by using WhatsApp, Google Form, and Zoom applications. Findings in this study included: 1) The average percentage of the school supervisors' success in planning the online supervision was 77% with the Sufficient category; 2) The online supervision was conducted from September 8 to September 11, 2021, with an average success rate of 81%, which was in the "Good" category; and 3) The evaluation of the results of online supervision indicated that some teachers were able to carry out the preliminary activities, main activities, and post activities properly, based on the guidelines. This study concluded that the online supervision conducted by the school supervisors at Elementary School in Kabupaten Rokan Hilir followed the established criteria and systematics. The technology mastery, especially using WhatsApp, Google Form, and Zoom applications, was crucial for teachers, principals, and school supervisors